Compact Meander Line Telemetry Antenna for Implantable Pacemaker Applications - N. H. Sulaiman; N. A. Samsuri; M. K. A. Rahim; F. C. Seman; M. Inam (Institute of Advanced Engineering and Science, 2018)
The demand for health technology is increasing rapidly especially in telemetry applications. These applications generally use implanted antennas to be utilized for data transfer from patients to another reader device. This procedure can make the health care more efficient, since it provides fast diagnosis and treatment to the patient. This work presents a design of telemetry antenna to be used in Pacemaker application in Medical Implant Communication Services (MICS) (401 MHz-406 MHz). By introducing Compact Meander Line Telemetry Antenna (CMLTA), length (Ls) and width (Ws) of substrate have been reduced by 36.84% and 40% respectively. The proposed antenna offers advantages of easy fabrications, low cost and light weight with a 133 MHz bandwidth.